RELIABILITY ANALYSIS OF MULTIDISCIPLINARY COUPLED SYSTEM - HE Qian (Jixie qiangdu)
Based on first order reliability analysis method（ FORM）,concurrent subspace optimization（ CSSO） method was employed to research on the efficiency of reliability analysis of multidisciplinary coupled system. The precision and efficiency of the methods was discussed. The result shows that the reliability analysis method based on CSSO is more efficient than single level method.